Optical observations of selected asteroids with measurable Yarkovsky effect - Pomazan, A.V.; Maigurova, N.V. (Advances in Astronomy and Space Physics, 2013)
The results of the observations of 10 asteroids for 2009-2012 and their analysis are presented here. The asteroids were selected based on the available list of asteroids with relatively large deviations from the unperturbed semimajor axis of the orbit that can be caused by Yarkovsky effect. The observations were made at RTT-150 (NO TUBITAK, Turkey) and Mobitel (RI NAO, Ukraine). We have calculated the differences between the observed (O) and the calculated (C) positions, as well as the standard deviations (RMS) of the measurements. For the telescope RTT-150, the RMS is approximately 0.05ʺ in both coordinates, and for the telescope Mobitel, the RMS is less than 0.1ʺ.